Method for assisted-GPS positioning based on ambiguity resolution in weak signal environment - SONG Cheng; WANG Fei-xue; ZHUANG Zhao-wen (Tongxin xuebao)
An assisted-GPS positioning algorithm was proposed.Based on this algorithm, the receiver needn’t accomplish the bit synchronization, frame synchronization and navigation data demodulation, which were usually necessary for the conventional GPS receiver, it could implement the positioning solution only by the measurement of pseudo-code phase and the assistance data（including ephemeris information and satellite clock corrections etc.）.Compared with the conventional GPS positioning algorithm, the proposed algorithm increases the ambiguity of the signal transmission time as an unknown parameter for the pseudorange equation.When the initial errors of approximate location and receiver’s clock bias were subjected to a constraint domain, the ambiguity of the signal transmission time could be eliminated.Then, the iteratively equation for this algorithm was derived, and the main steps were summarized.The simulation results show the validity of the algorithm.